When can Muslims withdraw or withhold life support? A narrative review of Islamic juridical rulings. Issue 1 (1st January 2020) - Mohiuddin, Afshan; Suleman, Mehrunisha; Rasheed, Shoaib; Padela, Aasim I.
ABSTRACT: When it is ethically justifiable to stop medical treatment? For many Muslim patients, families, and clinicians this ethical question remains a challenging one as Islamic ethico-legal guidance on such matters remains scattered and difficult to interpret. In light of this gap, we conducted a systematic literature review to aggregate rulings from Islamic jurists and juridical councils on whether, and when, it is permitted to withdraw and/or withhold life-sustaining care. A total of 16 fatwās were found, 8 of which were single-author rulings, and 8 represented the collective view of a juridical council. The fatwās are similar in that nearly all judge that Islamic law, provided certain conditions are met, permits abstaining from life-sustaining treatment. Notably, the justifying conditions appear to rely on physician assessment of the clinical prognosis. The fatwās differ when it comes to what conditions justify withdrawing or withholding life- sustaining care. Our analyses suggest that while notions of futility greatly impact the bioethical discourse regarding with holding and/or withdrawal of treatment, the conceptualization of futility lacks nuance. Therefore, clinicians, Islamic jurists, and bioethicists need to come together in order to unify a conception of medical futility and relate it to the ethics of withholding and/or withdrawal of treatment.